QUALITY OF SERVICE ANALYSIS OF WIFI NETWORK MODULE INTELLI BG96 USING MQTT AND HTTP PROTOCOL ON INTERNET OF THINGS PLATFORM SMART GREENHOUSE - Tri Nur Pamungkas, Muh.
Indonesia is a country that has a tropical climate which is very good for carrying out various activities in the field of agriculture or plantations. The implementation of a food security system can be done by cultivating plants with various agricultural systems that can answer problems related to lack of land, unstable climate, and the existence of a pandemic crisis that causes outdoor activities to be constrained. In responding to these challenges, hydroponic cultivation is a solution related to plant cultivation problems by applying the Smart Greenhouse application as a wake-up room that functions to maintain plants with maintained environmental conditions based on the use of Internet of Things (IoT) technology so that plant conditions can be practically monitored. This study designs, manufactures and tests a Smart Greenhouse monitoring system with a Intelli BG96 WiFi module microcontroller connected to an LDR light intensity sensor, a DHT11 temperature and humidity sensor, and a Water Level Sensor to detect water levels. The communication protocol used in this study is MQTT and HTTP which are connected to the Antares server. While testing the network QoS analysis using wireshark. The results of this research data indicate that the monitoring system is proven to be effective, it can be accessed using the web and smartphone with ideal values for temperature, light humidity, water level. The results of the tool test show that the average pakcoy plant by placing it in the Smart Greenhouse has a height growth of 6 cm during the 12 day experiment. Meanwhile, in the QoS test of MQTT and HTTP protocol data communication, the data in the test proves that MQTT requires less bandwidth than HTTP with a difference of 5542 bps. Packet loss in MQTT is more efficient than HTTP because the use of the smallest packet in the network handled by the system is a packet from MQTT with a smaller 0.12% difference in value. The HTTP delay and jitter values are superior in this experiment when compared to MQTT with a difference of 166 ms faster than MQTT. This is influenced by various factors including the 1 hour test of MQTT data only produced 7117 packets while HTTP produced 10670 packets so that the calculation results on packet delay have different value